Learning Time Allocation and Learning Resistance and Their Effect on Students' Interest in Learning Arabic - Jesi Ramadani; Fatma Yulia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Students’ interest in learning Arabic at the junior secondary school level remains a significant challenge, particularly regarding the effective management of instructional time. Inadequate or suboptimal lesson duration may reduce student engagement and diminish their enthusiasm for learning Arabic. Therefore, this study aims to examine the effect of lesson duration on students’ interest in learning Arabic at SMP Muhammadiyah 02 Medan. The research employed a quantitative approach using a survey method. The sample consisted of 47 students selected through a saturated sampling technique. Data were collected using a questionnaire that had met validity and reliability requirements and were analyzed through descriptive statistics, normality testing, linearity testing, and simple linear regression analysis. The findings revealed that both lesson duration and students’ interest in learning Arabic were at a moderate level. The results of the simple linear regression analysis demonstrated that lesson duration has a positive and statistically significant effect on students’ interest in learning Arabic, with a t-value of 2.204 and a significance level of 0.033 (p < 0.05). The regression equation obtained was Y = 18.339 + 0.248X, indicating that lesson duration contributes 9.7% to the variance in students’ learning interest. These findings suggest that optimizing instructional time can enhance students’ interest in learning Arabic. The study contributes empirical evidence highlighting the importance of effective lesson duration management as a practical strategy for improving Arabic language learning outcomes and fostering greater student engagement at the junior secondary education level.